Protection for Medical Workers Confronting the Challenges During the COVID-19 Outbreak-A Case of China - Chenyi Shao; Siwei Zheng; Shuangyi Sun; Zhen Xie; Xiaoting Pan (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
The COVID-19 outbreak is a major public health emergency initially occurred in Hubei, the epicenter in China, and then it rapidly turned into a global pandemic with much more than five million infected cases 28 May, 2020 [1]. Thanks to the joint efforts from all parties, especially the great contributions from Chinese medical workers, China's domestic situation has improved significantly, while it remains severe in the rest of world.